On the Coordination of Private Enforcement and Leniency System of Anti-monopoly Law based on International Experience - Liu, Linzhao (Journal of Theory and Practice of Management Science, 2023)
The so-called act is not enough to act on its own. The anti-monopoly law has been in force for ten years, and the relationship between public enforcement and private enforcement is studied by scholars. The coordination between leniency system and private execution is the most representative in the conflict between public and private execution of anti-monopoly law. But at present in our country there is no clear provision about the leniency system in anti-monopoly law and the coordination of private execution. This paper takes the foreign cases as a hair point, analyzes the leniency system and the private execution issue in the anti-monopoly law, and combined with the effective and successful foreign practical experience, under the framework of the anti-monopoly law as a forward-looking question, mainly from the leniency evidence materials protection and the liability of compensation Two aspects of analysis. In order to promote the implementation of anti - monopoly law of procedure refinement.